"Work curve" as a distinguishing mark of athletes' work performance - Mikicin Mirosław (Sciendo, 2014)
Study aim: The aim of the study was to determine work performance in the aspect of work rate, energy, persistence, adaptation rate, and accuracy based on the indices of an athlete's work curve.